Pengaruh Proses Annealing Terhadap Akurasi Dimensi Dan Kuat Tarik 3D Printing Menggunakan Filamen ST-PLA - Zarkasih, Zarkasih; Hasdiansah, Hasdiansah; Sugianto, Sugianto (Jurnal Inovasi Teknologi Terapan, 2024)
3D printing is a tool used to make objects / test specimens in 3 dimensions, using the main material made from polymer. In 3D printers there are two types of filaments that are often used today, namely Polylactic acid or polylactide (PLA) material and Acrylonitrile butadiene styrene (ABS), the material used in this study is PLA material, this material was chosen because it has several advantages. Poly(lactic acid) (PLA) biodegradable thermoplastics have been used in various industrial fields including automotive, computer, food, and electrical equipment also used in medical devices, PLA is a biodegradable thermoplastic sourced from natural starches such as corn and sugarcane. Therefore, this study aims to find the highest tensile strength in PLA materials using several levels of testing, The highest tensile test result at one parameter level will be carried out by the annealing process to determine the effect of the annealing process on the tensile test specimen. The research method used in this study is the Taguchi method designed L9 with 3 factors and 3 levels, using the Analysis of Variance (ANOVA) analysis method. The test results showed that the highest tensile strength was located in study number 5, which was 44.866 Mpa, and the lowest average tensile test value was in study number 4, which was 40.033 Mpa.